PERAN PEMERINTAH KABUTAPEN BENGKALIS DALAM MENGURUS TENAGA KERJA LOKAL TAHUN 2022-2023 - Putra, Dovi Rahman; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Unemployment alleviation is one form of implementation of Mandatory Government Affairs that must be carried out by every local government. High unemployment impacts the economy, social, and psychological aspects of the community.Bengkalis Regency has established employment regulations, such as Regional Regulation Number 3 of 2012, Regent Regulation Number 38 of 2021, and Regional Regulation Number 3 of 2022, which require companies to prioritize local workers.The Manpower and Transmigration Office is authorized to organize training, expand employment opportunities, and build industrial relations. This study aims to determine the role of the Bengkalis Regency Government in managing the local workforce from 2022 to 2023. The theory used is the theory of the government's role as a regulator, dynamic agent, and facilitator proposed by Ryaas Rasyid.This study uses a descriptive qualitative approach with interview and documentation techniques. Data analysis was carried out through the stages of collection, reduction, presentation, drawing conclusions, and verification. The research location includes Bathin Solapan, Mandau, and Pinggir Districts in Bengkalis Regency. The results of this study indicate that the role of the Bengkalis Regency Government in managing the local workforce in 2022-2023 is still not optimal. As a regulator, the Manpower and Transmigration Office has implemented Regional Regulation No. 3 of 2022 through various strategies and programs, but has not been accompanied by technical regulations in the form of a Regent's Regulation, so that enforcement of the regulation is not optimal. . In its role as a dynamic, the local government has provided job training, but the impact has not been optimal due to the lack of post-training evaluation Keywords: Role of Government, Local Workforce